Clave dicotómica de las especies del género Pluteus Fr. (Pluteaceae) conocidas de la región de Nueva Galicia y algunas áreas aledañas, México - Rodríguez, Olivia; Guzmán-Dávalos, Laura (Instituto de Ecología, A.C., 2001)
A dichotomous key of 21 species of Pluteus Fr. recorded from Nueva Galicia, Mexico, is presented. This paper is part of the results obtained from the study of this genus in the region. Short comments of the 21 species and examined materials are included.